Ketergantungan pada Konten Dakwah Singkat dan Dampaknya terhadap Pemahaman Mendalam Keislaman Pada Gen Z - Hanina Najma Adzkia; Farhan Fahreza; Syahla Salsabila; Aura; Abdul Fadhil (Yayasan Al-Afif, 2026)
The widespread use of short-form Islamic preaching content on social media has transformed the religious learning patterns of Generation Z. Although brief and engaging digital preaching provides easy access to Islamic knowledge, it may also foster dependence on instant religious information. This study aims to analyze Generation Z's dependence on short-form da'wah content and its impact on developing a deeper understanding of Islam. The research employed a qualitative library research method by collecting and analyzing relevant books, journal articles, and scientific publications concerning digital da'wah, Generation Z, and Islamic learning. The findings indicate that short-form da'wah effectively attracts attention and broadens access to religious information. However, excessive reliance on such content without further systematic learning may result in fragmented, superficial, and less critical religious understanding. Therefore, short-form da'wah should function as an entry point that encourages more comprehensive and in-depth Islamic learning.